OCCULT HEPATITIS B VIRUS INFECTION AMONG PATIENTS WITH LIVER DYSFUNCTION IN VARNA, BULGARIA - Denitsa Tsaneva-Damyanova; Elitsa Golkocheva-Markova; Liliya Ivanova; Tsvetelina Kostadinova; Zhivka Stoykova (Peytchinski Publishing, 2018)
Background: Occult hepatitis B infection (OBI) is a challenge in virology and a clinically relevant topic. The present study assessed the presence of HBV-DNA in serum samples of HBsAg negative, patients with data of liver dysfunction, positive for anti- HBc total Ab with or without anti-Hbs Ab. Purpose: The goal of this study was to evaluate the prevalence of occult hepatitis B in Varna region, among patients with chronic liver dysfunction. Materials and methods: The investigation was conducted among 79 people, predominantly patients at Gastroenterology Clinic in the University Hospital St. "Marina", Varna, Bulgaria. Quantitative determination of HBV DNA was performed in the National Reference Laboratory for Hepatitis viruses at the National Centre of Infectious and Parasitic Diseases, Sofia, Bulgaria. Results: From 79 investigated patients with liver dysfunction16 (20. 25%), were considered as occult HBV carriers. Fourteen of them (17.72%) were positive for HBV DNA with very low values, below 200 IU/ml. Two of the cases (2.53%) were with serum levels comparable to those usually detected in the different phases of serologically evident (overt) infection and are considered as "false" OBI. Conclusions: Our data showed that OBI is more widespread than expected and can be identified as a significant risk factor for the presence of more severe liver damages and an important oncogenic factor for developing cirrhosis and hepatocellular carcinoma.